Statistical and econometric methods for transportation data analysis - Washington, Simon; Karlaftis, Matthew G.; Mannering, Fred L. (Boca Raton, FL : CRC Press, 2011)
The book describes and illustrates some of the tools commonly used in transportaion data analysis. It serves as a technical reference for researchers and practitioners wishing to examine and understand a broad range of analytical tools required to solve transportation problems; providing a wide range of transportation examples and case studies covering applications in various aspects of transportation planning, engineering, safety and economics. It provides statistical fundamentals and presents continous dependent variable models. amongst other issues.
A Chapman & Hall book.
Includes bibliographical references (p. 489-509) and index.
opc 10/05/13
Loans
Keywords: Transportation -- Statistical methods; Transportation -- Econometric models